Clinimetric analysis of outcome measures for airway clearance in people with cystic fibrosis: a systematic review. (September 2022) - Stanford, Gemma E.; Jones, Mandy; Charman, Susan C.; Bilton, Diana; Usmani, Omar S.; Davies, Jane C.; Simmonds, Nicholas J.
Background: Airway clearance techniques (ACTs) are integral to cystic fibrosis (CF) management. However, there is no consensus as to which outcome measures (OMs) are best for assessing ACT efficacy. Objectives: To summarise OMs that have been assessed for their clinimetric properties (including validity, feasibility, reliability, and reproducibility) within the context of ACT research in CF. Design and Methods: A systematic review was conducted according to Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA) standards. Any parallel or cross-over randomised controlled trial (RCT) investigating outcome measures for ACT in the CF population were eligible for inclusion. The search was performed in five medical databases, clinicaltrials.gov, and abstracts from international CF conferences. The authors planned to independently assess study quality and risk of bias using theCO nsensus-basedS tandards for the selection of health statusM easurementI nstrumeN ts (COSMIN) risk of bias checklist with external validity assessment based upon study details (participants and study intervention). Two review authors (GS and MJ) independently screened search results against inclusion criteria, and further data extraction were planned but not required. Results: No completed RCTs from the 187 studies identified met inclusion criteria for the primary or post hoc secondary objective. Two ongoing trials were identified. Discussion and conclusion: This empty systematic review highlights that high-quality RCTs are urgently needed to investigate and validate the clinimetric properties of OMs used to assess ACT efficacy. With the changing demographics of CF combined with the introduction of cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies, an accurate assessment of the current benefit of ACT or the effect of ACT withdrawal is a high priority for clinical practice and future research; OMs which have been validated for this purpose are essential. Registration: This systematic review was registered on the PROSPERO database (CRD42020206033).